2012
DOI: 10.1128/aem.00675-12
|View full text |Cite
|
Sign up to set email alerts
|

Methanogenic Population and CH 4 Production in Swedish Dairy Cows Fed Different Levels of Forage

Abstract: bMethanogenic community structure, methane production (CH 4 ), and volatile fatty acid (VFA) profiles were investigated in Swedish dairy cows fed a diet with a forage/concentrate ratio of 500/500 or 900/100 g/kg of dry matter (DM) of total DM intake (DMI). The rumen methanogenic population was evaluated using terminal restriction fragment length polymorphism (T-RFLP) analysis, 16S rRNA gene libraries, and quantitative real-time PCR (qRT-PCR). Mean CH 4 yields did not differ (P > 0.05) between diets, being 16.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
63
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 40 publications
17
63
0
Order By: Relevance
“…Methanogen densities also agreed with those observed in Swedish dairy cattle, alpaca, and Brahman-cross cattle [16,25,26]. However, lower methanogen densities were observed in buffalo, Atlay sheep, and Svalbard reindeer [10,26,27].…”
Section: Impala Rumen Methanogen and Bacterial Densitiessupporting
confidence: 70%
“…Methanogen densities also agreed with those observed in Swedish dairy cattle, alpaca, and Brahman-cross cattle [16,25,26]. However, lower methanogen densities were observed in buffalo, Atlay sheep, and Svalbard reindeer [10,26,27].…”
Section: Impala Rumen Methanogen and Bacterial Densitiessupporting
confidence: 70%
“…However, some studies have shown no such correlation with their overall abundance while in others the correlation has been weak. Morgavi et al [37], Zhou et al [38], Danielsson et al [39] and Danielsson [40] found no correspondence between the numbers of methanogens and methane emissions from dairy cows when measured using metagenomics and qPCR techniques. Kittelmann et al [41] and Shi et al [42] formed a similar conclusion in sheep.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al [38], Danielsson et al [39], Shi et al [42] and Danielsson [40] all found a positive correlation between the relative abundance of Methanobrevibacter SGMT clade and methane emissions. Danielsson [40] interpreted this correlation in terms of different affinities for H 2 in the two groups, with the SGMT clade possessing methyl coenzyme M reductase isozymes McrI and McrII [12], which enables the archaea to utilise H 2 at higher concentrations, against the RO clade that possess only McrI [3, 12].…”
Section: Introductionmentioning
confidence: 99%
“…The sequencing results showed that M. woesei was abundant in four out of eight soil treatments at the end of the incubation period, notably in all fertilised soils. Methanogens related to the genus Methanobrevibacter are the most abundant archaea in the gut of herbivores [50,51]. Thus, it seems very likely that these methanogens may have originated from the manure and may have survived in the microcosms for six months, which emphasised the survival potential of methanogens even in subalpine upland soils.…”
Section: Methane Production and Consumptionmentioning
confidence: 99%